2019
DOI: 10.1371/journal.pone.0210004
|View full text |Cite
|
Sign up to set email alerts
|

Increased von Willebrand factor parameters in children with febrile seizures

Abstract: IntroductionPrimary blood coagulation and wound sealing are orchestrated by von Willebrand factor (VWF), a large multimeric glycoprotein. Upon release of arginine vasopressin (AVP), VWF containing high molecular weight multimers is secreted. By measuring copeptin, the C-terminal part of the AVP prohormone, we recently found strongly increased AVP levels in children with febrile seizures (FS) as compared to children with fever but without seizures. It is unknown if increased AVP levels in FS are of any biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Febrile seizures (FS) are one of the most common clinical diseases in pediatric neurology. It occurs between 6 months and 6 years of age and occurs in ~2–5% of children in the United States and Western Europe, ~5–14% in Asian countries, and 3–5% in China ( 1 3 ). According to the age, frequency, duration, and type of seizures, FS is divided into simple febrile seizures (SFS) and complex febrile seizures (CFS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Febrile seizures (FS) are one of the most common clinical diseases in pediatric neurology. It occurs between 6 months and 6 years of age and occurs in ~2–5% of children in the United States and Western Europe, ~5–14% in Asian countries, and 3–5% in China ( 1 3 ). According to the age, frequency, duration, and type of seizures, FS is divided into simple febrile seizures (SFS) and complex febrile seizures (CFS).…”
Section: Introductionmentioning
confidence: 99%
“…Imuekemhe et al in 1989 and 1996 found that lactic acid in the serum and cerebrospinal fluid of children with FS was significantly increased ( 6 ). Wellmann et al found that the serum copeptin and Von Willebrand factor (VWF) of children with FS were significantly higher than those of the control group ( 3 , 7 ). The levels of proinflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and anti-inflammatory cytokines, such as interleukin-4 (IL-4), in the peripheral blood of children with FS also exhibited significant changes, suggesting that these inflammatory molecules may play an important role in the pathogenesis of FS ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The routine use of prolactin is not recommended due to limited accuracy. Moreover, copeptin levels were significantly higher in the FS group than in the control group and may be more useful for distinction of the underlying cause of the convulsive event ( Stocklin et al, 2015 ; Pechmann et al, 2019 ). In contrast to these findings, our results could not provide additional support that copeptin and prolactin have the potential to predict upcoming convulsive events because none of the two biomarkers were related to recurrent seizures.…”
Section: Discussionmentioning
confidence: 94%
“…A PubMed/Medline search of these 100 differentially expressed peptides/proteins in Table 3 and Table 4 showed 70% were related to neurological function, 45% to immune/inflammation, 32% to seizures/epilepsy, 24% to ion-channels, and 10% to blood–brain barrier (BBB). Seizure/epilepsy related proteins (shaded cells in Table 3 and Table 4 ) include: SLIT2 (Slit guidance ligand 2 [ 29 ]), EPHB2 (EphrinB receptor 2, [ 30 ]), LAMA2 (Laminin alpha-2, [ 31 ]), ADAM11 (ADAM (A disintegrin and metalloprotease domain 11, [ 32 ]), P2RX7 (Purinergic receptor P2X 7, [ 33 ]), SLC4A4 (Solute carrier family 4 member 4, [ 34 ]), KCNQ2 (Potassium Voltage-Gated Channel Subfamily Q Member 2, [ 9 ]), VWF (von Willebrand factor, [ 35 ]), RYR2 (Ryanodine receptor 2, [ 36 ]), RECK (Reversion Inducing Cysteine Rich Protein With Kazal Motifs, [ 37 ]), ATP7B (ATPase Copper Transporting Beta, [ 38 ]), NF1 (Neurofibromin 1, [ 39 ]), HDC (Histidine Decarboxylase, [ 40 ]). Two other important seizure/epilepsy related proteins in Table 3 and Table 4 are CACNA2D2 (Calcium Voltage-Gated Channel Auxiliary Subunit Alpha2 delta 2, [ 41 ]) and ASTN2 (Astrotactin 2, [ 42 ]).…”
Section: Resultsmentioning
confidence: 99%